Disease controllability moderates the effect of coping efficacy on positive affect. Issue 4 (2nd April 2016) - Wiley, Joshua F.; Cleary, Elizabeth H.; Karan, Alexander; Stanton, Annette L.
Abstract : Objective: This study aims to test experimentally whether coping strategies (approach- vs. avoidance-oriented coping) have differential effects under conditions of high or low stressor controllability. Design: Undergraduates (62 women, 30 men) participated in a 2 × 2 experimental study where they were introduced to a fictitious disease (tisomerase enzyme deficiency) said to be either controllable or uncontrollable and an approach- or avoidance-oriented coping behaviour induction. Main Outcome Measures: Changes in positive and negative affect. Results: A significant disease control x coping interaction on positive affect ( f 2 = .07, p = .011) revealed that approach-coping condition participants had higher positive affect than avoidance-coping condition participants when disease control was high ( d = .94, p = .003), but not when it was low ( d = .11, p = .93). The experimental conditions did not significantly influence negative affect. Conclusion: Results demonstrate that disease control moderates the salubrious effects of approach-oriented coping on positive affect. For controllable, but not uncontrollable, health stressors, promoting problem-focused approach-oriented coping strategies may be recommended.